Quo Vadis Pemutusan Hubungan Kerja Setelah Amar Putusan Mahkamah Konstitusi Nomor 168/PUU-XXI/2023 - Prasetyo, Kurniadi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
After the Constitutional Court (MK) published Decision Number 168/PUU-XXI/2023, which was read aloud in an open plenary session of the Constitutional Court on October 31, 2024, employment law standards underwent changes. The court stressed that employers and employees must engage in bipartite discussions through debate to reach an agreement if workers/laborers reject Termination of Employment (PHK). Additionally, the layoff can only be carried out following a decision from an industrial relations dispute resolution body whose ruling has permanent legal force (inkracht) if bipartite negotiations fail to result in an agreement. With a focus on the inventory of positive law, legal doctrine, and principles, this study employs a normative legal method. Employers must therefore take into account the following dynamics: employers are not allowed to implement layoffs until they have received a decision from an industrial relations dispute resolution body that has permanent legal force, and every worker rejection of layoffs must be preceded by bipartite negotiations through deliberation to reach consensus.